Disentangled, decentred and democratised: Youth Studies for the global South. (2nd January 2019) - Cooper, Adam; Swartz, Sharlene; Mahali, Alude
ABSTRACT: Youth Studies' theories often assume universal generalisability despite rarely making the global South, or its youthful populations, ontologies, values and politics the focus of research. This paper grapples with the idea of a Youth Studies 'for' the global South, questioning whether theories/approaches that centre on the global North can be usefully applied in the global South, how and for what purpose. After describing two mainstream domains of Youth Studies scholarship, questioning how they may become applicable to Africa, Latin America and developing countries in Asia, we explicate the geo-politically situated nature of knowledge production. We ask how theories that originate elsewhere can be adapted and put to work in new contexts, contributing towards a Youth Studies that enhances the lives of youth on the global periphery. In Southern sites urgent material challenges dominate young people's lives, requiring theories that are able to analyse the multi-dimensional contextual constraints youth experience. Knowledges can be useful regardless of where they originate, but only when they become intentionally entangled in local realities and are adapted accordingly. We argue, however, that a Youth Studies for the global South needs to demonstrate its relevance beyond applying theories to new local sites. It should be able to say something more general about the human condition. In the current conjuncture of economic instability, we believe that contexts where youth have had to adapt, hustle and survive in precarious conditions for an extended period of time might demonstrate something unique about the human condition, but only if we make these places the focus of our research gaze. The paper concludes with suggestions to enable a Youth Studies for the global South, one which may contribute to this emerging field more effectively through intentional strategies of disentangling, decentring and ultimately democratising the field.